THE ETHICS OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN FACING LEARNING IN THE DIGITAL ERA AT MTS MIFTAHUL ANWAR - Enis Auliyaillah; Robiatul Adawiyah; Imam Buchori; Widiyana; Abd. Mukid (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The rapid advancement of digital-based tools has triggered fundamental and far‑reaching changes within the education system, including the way material is delivered in Islamic Religious Education (IRE). On one hand, these developments bring significant conveniences: access to knowledge has never been broader, various supporting learning resources are readily available, and the connection between educators and students has grown increasingly close. Yet, behind all these benefits lie considerable challenges most notably regarding the preservation of moral values and proper conduct. This reality demands that IRE teachers possess dual capabilities: they must be skilled in operating digital facilities, while also remaining adept at instilling noble principles aligned with Islamic teachings. This study aims to examine how professional ethics are viewed within the framework of Islamic education, identify measures that can be taken to strengthen these ethical standards in the modern era, and illustrate how they are practically implemented in teaching and learning activities at MTs Miftahul Anwar. The research adopts a qualitative approach with a descriptive design. All data were gathered through direct observation, in‑depth interviews, and document review, and subsequently processed using an interactive analysis model consisting of data reduction, report compilation, and conclusion drawing. The findings confirm that ethical standards for IRE educators essentially represent a balanced combination of noble personal character, professional responsibility, and firm religious commitment all rooted directly in Islamic teachings. Reinforcing this moral foundation can be achieved through several concrete steps: understanding the norms governing behavior in digital spaces, serving as a role model by using technology correctly and wisely, presenting relevant and educational content, and consistently encouraging students to act politely and ethically whenever engaging with online media. Implementing these values has proven to yield positive outcomes regarding students’ habits in using technology; they become more disciplined, capable of filtering information critically, thoughtful in their actions, and fully accountable for their conduct. Based on these results, it can be concluded that embedding strong ethical values within IRE instruction plays a decisive role in shaping the character and identity of the younger generation, even amid the rapid technological progress of today’s world.